The Great thoughts - Seldes, George, 1890- (New York : Ballantine Books, 1985)
Presents the ideas that have determined the intellectual history of the world. Arranged alphabetically by thinker and indexed by theme.
Includes index.
Adult
Keywords: Quotations, English; Quotations